Quality of Vegetable Seeds Collected from Mymensingh Region in Bangladesh - Hossain, I.; Dey, P.; Dilruba, K. (International Journal of Applied Sciences and Biotechnology, 2014)
Seed quality and health status of 11 vegetable crop seeds of viz. Cabbage (Brassica oleraceae var. capitata), Indian cabbage (Brassica oleraceae var. indica), Indian spinach (Basella alba), Spinach (Beta vulgaris var. bengalensis), Red amaranth (Amaranthus tricolor), Bitter gourd (Momordic acharantia), Bottle gourd (Lagenaria siceraria), Sweet gourd (Cucurbita moschata), Carrot (Daucuscarrota var. sativa), Radish (Raphanus sativus), and Turnip (Brassica rapa) collected from the greater Mymensingh region of Bangladesh were tested. The germination percentage of seeds of the collected samples ranged from 11 to 100. The highest germination was recorded in indian cabbage (100%) followed by carrot (92%) and radish (90%), while the lowest was recorded in indian spinach seeds (11%). Altogether 10 fungi were found associated with the seeds which were Alternaria spp., Aspergillus flavus, Aspergillus niger, Botrytis cinerea, Chaetomium funicola, Curvularia spp., Fusarium spp., Penicillium spp., Phoma spp. and Rhizopus spp.. The highest total seed-borne fungal infection was found in bottle gourd (155%) followed by sweet gourd (145%). The lowest infection was found in turnip seeds (6%). The maximum number of dead seeds was found in indian spinach (89%) and no dead seed was found in indian cabbage. Among the vegetables seed samples, seedling vigour ranged from 59 to 3083, where the highest seedling vigour was observed in sweet gourd (3083) and the lowest was in indian spinach (59). DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9926 Int J Appl Sci Biotechnol, Vol. 2(1): 103-108